Enhancing the competence of enterprise network using contemporary networking paradigms - Ahuja, Aditya; Dewan, Kamal; Gupta, Nikita; Sood, Meenakshi (Discoveries in Agriculture and Food Sciences, 2014)
Networking has traversed from days where networks were considered a background component of businesses to today’s electronic age, where networks are an imperative resource, and directly determine revenue generation for an organization. In today’s dynamic arena of networking, the crafting of networks has escalated from using just an elemental set of features, to consolidating modernistic technologies and services, in an effort to come up with state of the art networks which can meet the aim of connectivity, security, scalability, simplicity of operation, and flexible accommodation of new trends and technologies. The roots of this paper lie in the Enterprise network, and while adhering to the need of the hour in corporate sector, we propose architecture for Enterprise network, using avant-garde technologies such as Frame Relay, Port Security, Access Control Lists (Firewalling), VoIP, VPN, Ether Channel, Redistribution of Routing Protocols and ISP Redundancy. The network architecture has been designed on Cisco’s network simulation software: Cisco Packet Tracer. The principle behind the proposed network architecture can be applied in designing the networks of a host of other campuses.